Ácido ascórbico no condicionamento de sementes de feijão-caupi submetidas aos estresses hídrico e salino - Nunes, Luma Rayane de Lima (2019)
Stressful conditions, such as environmental factors, cause physiological impacts to plants, including cowpea, for producing reactive oxygen species, in which their accumulation causes degradation of the organelles and the plasma membrane. Ascorbic acid is an important metabolite involved in the defense against oxidative damage. The objective of this study was to evaluate the effects of conditioning cowpea seeds with ascorbic acid to attenuate the damage caused by saline and water stresses. Seeds of BRS Marataoã and Setentão genotypes were conditioned at concentrations 0,0 (control); 0.25; 0.50; 0.75 and 1.00 mM of AsA and seeded on paper rolls (Germitest®), moistened in NaCl and mannitol solutions at 0.0 (control) potentials; 1.5; 3.0, 4.5; 6.0 and 7.5 dS m-1; and 0.0 (control); - 0.3; - 0.6; - 0.9 and -1.2 MPa, respectively, and placed in a germination chamber at a temperature of 25 ºC. Conducted in a completely randomized design, with four replicates of 50 seeds per treatment. The analyzed variables were percentage of germination, first germination count, germination speed index, shoot and root length, total seedling dry mass, and extravasation of leaf and root electrolytes. The conditioning of the seeds with ascorbic acid at concentrations of 0.50 and 0.75 mM for BRS Marataoã and Setentão genotypes, respectively, allowed the development of more vigorous seedlings and the reduction of membrane damage caused by oxidative stress both in the absence of salt and for the saline levels tested, including the highest.